18.2: Invited Paper: Semipolar Micro‐LED for Full‐color Display and Visible Light Communication. (26th August 2021) - Lin, Wansheng; Huang, Yu-Ming; Konthoujam, James Singh; Lin, Yue; Lu, Yijun; Chen, Zhong; Wu, Tingzhu; Kuo, Hao-Chung
Abstract : Micro‐LEDs (μ‐LEDs) are well known to have a thriving future in the next‐generation display field. However, conventional μ‐LEDs grown on c‐plane GaN have a severe wavelength shift due to the quantum confined Stark effect (QCSE), which seriously affects the color quality of μ‐LEDs display. In order to fundamentally solve this problem, we grown blue μ‐LED with a 30 µm diameter on the (20–21) semipolar GaN combined with perovskite quantum dots (PQDs) color conversion layer, to achieve high‐quality full‐color μ‐LED, realizing a wide color gamut with 99.2% National Television Standards Committee (NTSC) space and 93.0% Rec 2020 in the CIE 1931, and the peak wavelength hardly shifts, indicating an excellent inhibitory on QCSE. Meanwhile, the semipolar blue μ‐LED excitation light can achieve a wide 3‐dB bandwidth of 652 MHz due to the faster carrier recombination rate, making semipolar LEDs more attractive in the high‐speed visible light communication (VLC).